2012
DOI: 10.1007/s12262-012-0608-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surgical Stress on Early Nonspecific Immune Response in Children

Abstract: Surgery alters the body's homeostatic balance and defense mechanisms. In adults transient postoperative cellular and humoral immunosuppression after different degrees of operative stress has been reported. In children the immunologic consequences of operations are not elaborated. This study investigates the effect of minor and major surgery on early nonspecific immune response in terms of neutrophil counts and function. Forty-three children undergoing minor and major elective procedures were studied. Blood sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…The postoperative concentrations of white blood cells peak at 24–48 h and gradually decrease [ 16 ]. Our study used ANC on the third postoperative day and showed that in more than half of the studied subjects (57.69%), the ANC remained elevated at 72 h, similar to findings from Romeo et al’s study on monocyte and neutrophil activity after minor surgical stress, and Prabhu PS et al’s study on effects of surgical stress on early nonspecific immune response in children [ 18 , 19 ]. These patients must be carefully monitored because they present a worse prognosis concerning the evolution of the oncological disease [ 20 ].…”
Section: Discussionsupporting
confidence: 86%
“…The postoperative concentrations of white blood cells peak at 24–48 h and gradually decrease [ 16 ]. Our study used ANC on the third postoperative day and showed that in more than half of the studied subjects (57.69%), the ANC remained elevated at 72 h, similar to findings from Romeo et al’s study on monocyte and neutrophil activity after minor surgical stress, and Prabhu PS et al’s study on effects of surgical stress on early nonspecific immune response in children [ 18 , 19 ]. These patients must be carefully monitored because they present a worse prognosis concerning the evolution of the oncological disease [ 20 ].…”
Section: Discussionsupporting
confidence: 86%
“…In terms of stress responses as a result of surgical trauma, tachycardia was found up to the mark as only in 8 patients among 100 patients but there was a significant increase in neutrophil count at the end of surgery as the mean % neutrophil count S2 was 74.88 when compared to S1 i.e. before surgery where mean count was 65.98, indicating that the neutrophil are in a heightened state of alertness, this study was supported by the results of P. Santosh Prabhu et al, later on the neutrophil count was decreased in early post-operative period as the mean count was decrease to 56.36 respectively, which might be resulted for early post-operative complications 14 . As per statistical analysis, there was statistical significance (P > 0.05, by using paired-t test).…”
Section: Discussionsupporting
confidence: 75%
“…[5,13] Children under the age of 18 months were excluded from this study. In addition, all children with a medical condition affecting the respiratory tract, such as bronchial asthma, patients with a history of parental smoking or chronic exposure to air pollution, those with a history of immune deficiency, those taking any medication that had an effect on their immune status, such as corticosteroids or immunosuppressive agents, those who had acute or chronic inflammation of other systems or organs, congenital diseases, or a history of recent major surgery, which included (duration of surgery more than 90 minutes, intraperitoneal or extensive extraperitoneal dissection, or a postoperative stay of more than 24 hours), [14] were excluded from this study.…”
Section: Patient and Methodsmentioning
confidence: 99%